LEGAL REGULATION OF PREVENTION AND ELIMINATION OF OIL SPILL INCIDENTS IN THE ARCTIC REGION - V. Kripakova, Alexandra (Gênero & Direito, 2020)
Nowadays, as the significance of the Arctic is increasing, the international community faces new challenges. At the present time, Arctic states (Russia, USA, Canada, Denmark and Norway) continue to prepare to the beginning of the large-scale oil and gas resource development of the Arctic offshore. However, discovering and exploitation of the hydrocarbon deposits endanger the fragile ecosystem of the region. In this type of economic activity, oil spills present the greatest hazard to the environment. The article considers activity of the Arctic Council in this area, as well as the international and national legal regulatory mechanisms to ensure environmental security in the Arctic.